Influence of Training on Farmer’s Productivity in Poultry Production in Kogi State, Nigeria - Ibitoye , S.J.; Onimisi, J.A. (International Journal of Poultry Science, 2013)
The study examined the influence of training on the productivity of poultry farmers in kogi state, Nigeria. The data used for the study were obtained using structured questionnaire and was administered to 200 poultry extension contact farmers. Descriptive statistics, percentages, sigma scoring and multiple regression models were used to analyze the data. The study revealed that majority of the poultry contact farmers were males (95.50%). The average birds per farmers was found to be 380 birds, while the mean age, farming experience and farm income were 46 years, 9 years and N185,000.00, respectively. Frequency of participation in training programmes revealed that extension training has the highest level of frequency followed by formal education. The sigma scores recorded for both extension training (5.950) and formal education (5.974), confirmed the high level of usage of the two training programmes. The regression results to determine the effect of the training programmes on the productivity of poultry farmers showed that all the training programmes were positively related to farmer’s income. Only extension training (7.305) and formal education (3.310) were significantly related to farmer’s income. It was therefore recommended that government should organize regular training for rural farmers as a way of improving their productivity.